Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18632/oncotarget.8815
|View full text |Cite
|
Sign up to set email alerts
|

Wogonoside prevents colitis-associated colorectal carcinogenesis and colon cancer progression in inflammation-related microenvironment via inhibiting NF-κB activation through PI3K/Akt pathway

Abstract: The inflammatory microenvironment has been reported to be correlated with tumor initiation and malignant development. In the previous studies we have found that wogonoside exerts anti-neoplastic and anti-inflammatory activities. In this study, we aimed to further investigate the chemopreventive effects of wogonoside on colitis-associated cancer and delineated the potential mechanisms. In the azoxymethane initiated and dextran sulfate sodium (AOM/DSS) promoted colorectal carcinogenesis mouse model, wogonoside s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…In the present study, wogonoside was observed to significantly suppress PI3K and p-AKT protein expression in LOVO cells. Sun et al (25) suggested that wogonoside prevents colitis-associated colorectal carcinogenesis through inhibiting nuclear transcription facto-κB (NF-κB) activation via the PI3K/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, wogonoside was observed to significantly suppress PI3K and p-AKT protein expression in LOVO cells. Sun et al (25) suggested that wogonoside prevents colitis-associated colorectal carcinogenesis through inhibiting nuclear transcription facto-κB (NF-κB) activation via the PI3K/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence indicates that wogonin (25 mg/mL) treatment obviously attenuates the inflammatory response of toll like receptor (TLR4)-myeloid differentiation factor (MyD) 88-mediated NF-κB pathway in lipopolysaccharide (LPS)-induced intestinal inflammation of Caco-2 cells in vitro, suggesting protective function on intestinal mucosal barrier [47]. As for wogonoside (12.5, 25 or 50 mg/kg), its application inhibits the activation of NF-κB-induced NLRP3 inflammasomes in DSS-induced colitis and colitis-associated tumorigenesis in mice [48,49].…”
Section: Heat-clearing and Dampness-drying Medicinementioning
confidence: 99%
“…Inhibit the protein expression of p-p65 [49] THP-1 cells Suppress NF-κB nuclear translocation [49] Berberine Colonic macrophages and epithelial cells…”
Section: Chinese Medicines Models Mechanisms Referencesmentioning
confidence: 99%
“…Wogonoside, as the glucuronide metabolite of wogonin, at dosages of 12.5, 25 or 50 mg/kg intragastrically, protects against DSS-induced experimental colitis in mice by inhibiting NF-jB and NLRP3 inflammasome activation [35]. Firstly, whether the effect of wogonoside is different from that of wogonin need further study.…”
Section: Discussionmentioning
confidence: 99%